2016
DOI: 10.1089/hum.2016.038
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Existing Oncolytic Virus M1 Is Nonpathogenic for the Nonhuman Primates After Multiple Rounds of Repeated Intravenous Injections

Abstract: Cancers figure among the leading causes of morbidity and mortality worldwide. The number of new cases is expected to rise by about 70% over the next 2 decades. Development of novel therapeutic agents is urgently needed for clinical cancer therapy. Alphavirus M1 is a Getah-like virus isolated from China with a genome of positive single-strand RNA. We have previously identified that alphavirus M1 is a naturally existing oncolytic virus with significant anticancer activity against different kinds of cancer (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…In our efforts to further translate OV M1 to the clinic, we have completed a safety evaluation of intravenously injected OV M1 in nonhuman primates (36). Here, we evaluated the safety of EerI alone and EerI/M1 in combination in treatment groups of six animals each.…”
Section: Combination Of Ov M1 and Vcpi Is Safe In Nonhuman Primatesmentioning
confidence: 99%
“…In our efforts to further translate OV M1 to the clinic, we have completed a safety evaluation of intravenously injected OV M1 in nonhuman primates (36). Here, we evaluated the safety of EerI alone and EerI/M1 in combination in treatment groups of six animals each.…”
Section: Combination Of Ov M1 and Vcpi Is Safe In Nonhuman Primatesmentioning
confidence: 99%
“…Studies in both dogs and non-human primates have reported autopsy results showing that oncolytic viral therapies are non-pathogenic to normal tissues 26 , 27 , 38 , 39 . Autopsy of the cats in this study revealed that a few tissues had lesions of undetermined etiology.…”
Section: Discussionmentioning
confidence: 99%
“…M1 has tumor selectivity related to zinc-finger antiviral protein (ZAP) deficiency in tumor cells and therefore can selectively replicate in tumor cells and induce apoptosis of the infected tumor cells by inducing irreversible endoplasmic reticulum (ER) stress [72]. M1 showed high tumor cell selectivity and tumor-killing activity during in vitro and in vivo experiments [73]. Moreover, its antitumor activity can be considerably increased by targeted inhibitors, such as valosin-containing protein (VCP) inhibitor and DNA-dependent kinase (DNA-PK) inhibitor [74,75], suggesting that combining M1 with these inhibitors is an important strategy.…”
Section: Wild-type Ovs In Oncolytic Virotherapymentioning
confidence: 99%